2021
DOI: 10.1186/s13007-021-00830-6
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of Raman and Infrared spectroscopy for rapid characterization of fucoidan extracts

Abstract: Background Fucoidans are sulfated polysaccharides from the cell-wall of brown algae. They have a wide range of applications in medicine, including regenerative medicine, ophthalmology, cancer, and autoimmune disease. Biological activity of fucoidans directly depends on their structure, which remains poorly understood. This is primarily because the polymeric nature of these molecules limits the use of nuclear magnetic resonance and mass spectrometry, classical tools of structural biology for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The IR spectra in Figure 1 confirmed the previous findings and showed that L. saccharina fucoidan is atypical, where the S=O band at 1240 cm −1 was wide and compressed, in addition to the C-O-S band at 874 cm −1 was reduced to a narrow band without showing any complicated pattern. Nevertheless, fucoidans derived from Fucales , i.e., F. spiralis and F. vesiculosus showed relatively similar IR spectra revealing the complicated region at 840 cm −1 being suggestive for the equatorial pattern of sulfation at C-4 and C-2 consistent with previous publications [ 41 , 54 ]. Though, with comparison with the purified form of F. vesiculosus , all extracted fucoidans showed an additional band at around 1420 cm −1 , which may correspond to -C-H deformation of formed melanoidins [ 54 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The IR spectra in Figure 1 confirmed the previous findings and showed that L. saccharina fucoidan is atypical, where the S=O band at 1240 cm −1 was wide and compressed, in addition to the C-O-S band at 874 cm −1 was reduced to a narrow band without showing any complicated pattern. Nevertheless, fucoidans derived from Fucales , i.e., F. spiralis and F. vesiculosus showed relatively similar IR spectra revealing the complicated region at 840 cm −1 being suggestive for the equatorial pattern of sulfation at C-4 and C-2 consistent with previous publications [ 41 , 54 ]. Though, with comparison with the purified form of F. vesiculosus , all extracted fucoidans showed an additional band at around 1420 cm −1 , which may correspond to -C-H deformation of formed melanoidins [ 54 ].…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, fucoidans derived from Fucales , i.e., F. spiralis and F. vesiculosus showed relatively similar IR spectra revealing the complicated region at 840 cm −1 being suggestive for the equatorial pattern of sulfation at C-4 and C-2 consistent with previous publications [ 41 , 54 ]. Though, with comparison with the purified form of F. vesiculosus , all extracted fucoidans showed an additional band at around 1420 cm −1 , which may correspond to -C-H deformation of formed melanoidins [ 54 ]. The higher intensity of this band in MAE products suggested that the higher temperature accompanied with MAE helped in Maillard reaction occurrence between protein and carbohydrate contents resulting in formation of melanoidins.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, in Raman, the sample is excited by scattering light that characterizes the rotational and vibrational modes of the sample. Therefore, FTIR is useful for identifying functional groups and determining the molecular structure of the sample, while Raman is better suited for identifying specific chemical bonds and detecting impurities in similar samples without the need of destructive and time-consuming analytical techniques . Additionally, when a molecule is Raman active, it is IR -inactive and vice versa .…”
Section: Discussionmentioning
confidence: 99%
“…NIR dispersive Raman scattering, typically excited in the range of 780-1100 nm, produces minimal uorescence and makes detection of the weak Raman signal easier. The use of a longer wavelength (such as 1064 nm) can improve the identi cation of minerals [24], dyes [25], cells [26], and cell extracts [27]. However, among the reported reviews, little attention has been paid to the application of 1064-nm Raman spectroscopy in the identi cation of Chinese medicinal materials and herbs.…”
Section: Introductionmentioning
confidence: 99%